1999
DOI: 10.1007/s004260050053
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving musical tension in long chord sequences

Abstract: We attempted to predict perceived musical tension in longer chord sequences by hierarchic and sequential models based on Lerdahl and Jackendoff's and Lerdahl's cognitive theories and on Parncutt's sensory-psychoacoustical theory. Musicians and nonmusicians were asked to rate the perceived tension of chords which were drawn either from a piece composed for the study (Exp. 1) or from a Chopin Prelude (Exps. 2-4). In Exps. 3 and 4, several experimental manipulations were made to emphasize either the global or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 33 publications
5
98
0
5
Order By: Relevance
“…It seems likely that the memory trace of the main key depends both on the harmonic relationships between main key and intervening local key and on the time elapsed since the first key. Bigand and Parncutt (1999), reported that listeners tend to lose the feeling of the main key rapidly after a distant modulation has occurred. The authors suggested that the short-term memory span "might increase when musical sequences modulate smoothly to closely related keys" (p. 252).…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that the memory trace of the main key depends both on the harmonic relationships between main key and intervening local key and on the time elapsed since the first key. Bigand and Parncutt (1999), reported that listeners tend to lose the feeling of the main key rapidly after a distant modulation has occurred. The authors suggested that the short-term memory span "might increase when musical sequences modulate smoothly to closely related keys" (p. 252).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the first 1'56^of the piece (34 bars; 132 beats), there was one beat containing a harmonic interval, and this happened to occur at a brief transition point in the piece where there were only two voices sounding. Furthermore, with a prevalence of only~0.7 %, it might well be the case that those infrequent harmonic events were not even experienced as Bconsonant,^as they would exhibit low pitch commonality with the surrounding pitches of the continuous inharmonic musical stream in which they are heard (cf., Bigand, Parncutt, & Lerdahl, 1996;Bigand & Parncutt, 1999). Thus we cannot only be confident that our selective pitch manipulations were successful in creating a (virtually) homogenously inharmonic stimulus, but also that these manipulations created a homogenously dissonant stimulus.…”
Section: Methodsmentioning
confidence: 99%
“…On a more speculative note, such a crossmodal mapping may be attributable to perceived similarities in (hedonic) patterns of tension and relaxation. In music, dissonances have often been regarded as tensions, which are resolved by relaxations in the form of consonances (Bigand & Parncutt, 1999;Schenker, 1979). Similarly, sour tastes often elicit a tensing of the facial muscles (eye-squinting, nose-wrinkling) as part of an aversive reaction (Steiner, Glaser, Hawilo, & Berridge, 2001).…”
Section: Interim Summarymentioning
confidence: 99%